Herpesviruses encode an unusual protein-serine/threonine kinase which is nonessential for growth in cultured cells. - de Wind, N (1992)
We have performed large-scale random oligonucleotide insertion mutagenesis on a 41-kbp genomic segment derived from the unique long (UL) region of the alphaherpesvirus pseudorabies virus (PRV). This procedure has resulted in the generation of a series of PRV strains, each carrying a single gene whose termination of translation is induced by the inserted oligonucleotide. To relate the genes that were involved in the mutagenization to genes previously identified in herpes simplex virus type 1, the prototype alphaherpesvirus, we have performed cross-hybridization studies. In this way, we have mapped the location of the homolog of a gene which was described to have sequence characteristics of a eukaryotic phosphotransferase. We characterized the phenotype of a mutant PRV strain lacking this putative phosphotransferase also the phenotype of a PRV strain lacking, in addition to the UL-encoded putative phosphotransferase, the protein kinase encoded within the unique short region of the virus. To assess the enzymatic activity of the UL region-encoded phosphotransferase, we expressed the gene transiently in a eukaryotic expression system. Immunoprecipitation of the protein followed by kinase assays and phosphoamino acid analyses revealed protein-serine/threonine kinase activity. Implications of sequence divergence of this protein from classical protein-serine/threonine kinases for kinase structure and function are discussed in view of the recent resolution of the structure of the catalytic domain of cyclic AMP-dependent protein kinase.